Efecto de los condimentos naturales en la estabilidad y aceptabilidad del chorizo escaldado de cerdo. Planta de cárnicos la maría U T E Q Quevedo, Ecuador 2013. - Suárez Larrosa, Johanna Karina (2013)
The investigation was carried out in the experimental property “The María” of the State Technical University of Quevedo in the plant of meat of the Ability of Cattle Sciences, located in the Km 7 via Quevedo-The Connection, the objective was to evaluate the effect of the natural condiments in the stability and acceptability of the scalded sausage of pig, to determine the best formulation according to the norms INEN, establishing the costs of production and profitability of the product. The characterization of the product was carried out to the five and fifteen days; to measure the stability in refrigeration it was studied the physical-chemical parameters, evaluated statistically totally at random by a design and the results were subjected to the variance analysis, with comparison of stockings (test of Tukey to (p0,05≤) establishing this way the existence or not of differences statistics between the treatments and the study of the parameters microbiológicos; in the acceptability study it was evaluated the organoleptic parameters whose results were subjected to the analysis of non-parametric variance Kruskal Wallis and to obtain the profitability of the product the relationship benefit-cost it was used; determining you as better formulation the formula 1, obtaining in the characteristics physical-chemical 61,90% of humidity, 38,10% of dry matter, 2,79% of ash, 18,05% of fat, 17,68 protein% and a pH of 5,47; in the characterization microbiológica it registered in aerobes total securities of 1,4 X 102 Ufc/g to the 5 days and 2,3 X 102 Ufc/g to the 15 days; in total colíformes absence of microorganisms existed in the two days and in the recount of mushrooms and total yeasts, he/she registered absence to the 5 days and 1,6 X 102 Ufc/g to the 15 days for what you concludes that it is a stable product, being also proven its acceptability in the organoleptic characterization, being with a moderate color reddish, enough scent to sausage, moderate scent to condiments, moderate flavor to sausage and condiment, moderate soft and juicy texture; the costs of production decrease existing a saving of 0,54% for produced kg, with a profitability of 72.52% and a (B/C) of 1.75. Key words: sausage, natural condiments, chemical preservatives, stability, acceptability